Evaluación de la calidad del servicio de préstamo de una biblioteca universitaria. - Riñón Sanz, Celia (Revista General de Información y Documentación, 2000)
The goal of this work is to assess a department of a university library. We have used the questionnaire SERVQUAL that is a methodology for mea suring ¡te quality of services developed y y y. A. Zeithaml, A. Parasuraman y Leonard L. Harry. It is itt two sections, one of them is related to user expecta tions and the other to the perceptiofis. The difference or discrepancy between the expectations and the perceptions will show us the measure of quality of service. We can conclude from the final results that ¡te main subject to be con sidered by the users is ¡te reliability, where we can observe a certain discre pancy, altbough it is minirnum. The key to supply a good quality service lies in maintaining the balance between expectations and perceptions and to actúe ve itt this way an improvement of servíce.